Influence of chemical treatment of mustrad-cake on its glucosinolate content and myrosinase activity - DAS, M M; SINGHAL, K K (The Indian Journal of Animal Sciences, 2014)
Finely ground mustard-cake was treated with copper sulphate and ferrous sulphate solutions individually at 0.25,0.50, 0.75, 1.00% (w/w) levels after adjusting pH ( 4, 5, 6, 7) maintaining 25% moisture followed by drying at 60°C till complete drying. Both the chemicals were also mixed homogeneously as such with mustard-cake at the above mentioned levels. Cu and Fe content in untreated, I % copper sulphate and 1% ferrous sulphate treated-cake was 38.25, 2592.38, 38.49 and 582.39, 580.85, 2690.30 ppm respectively. Total glucosinolate content of mustard-cake ( 42.33 ±0.03 mmol/g), comprising 3 butenyl isothiocyanate and 5 vinyl oxazolidine 2 thione (OZT), was reduced more pronouncely as a result of treatment with either of the chemical than their supplementation. Lowest glucosinolate content was recorded as 1.22±0.11 and 14.82±0.10 mmol/g after treatment with 1% copper sulphate and 1% ferrous sulphate at pH 4. Copper sulphate treatment was more efficient than ferrous sulphate treatment irrespective ofthe level of chemical. In none of the chemically treated and supplemented mustard-cake samples, OZT and nitriles were detected. Myrosinase activity of mustard-cake was drastically reduced in copper sulphate treated -cake ( pH 5) than in ferrous sulphate treated cake .